PENDAFTARAN PEMINDAHAN HAK ATAS TANAH OLEH KEPALA KANTOR PERTANAHAN DALAM “KEDAAN TERTENTU” MENURUT HUKUM TANAH NASIONAL - Khadijah; Achmad Faishal; Rahmida Erliyani (LPPM STIH Awang Long, 2023)
Arrangements for the transfer of land rights are regulated in the provisions of Article 37 Paragraph (1) and Paragraph (2) of Government Regulation Number 24 of 1997 concerning Land Registration. In this case the meaning of